1999
DOI: 10.1152/ajpheart.1999.277.1.h144
|View full text |Cite
|
Sign up to set email alerts
|

Myogenic reactivity of rat epineurial arterioles: potential role in local vasoregulatory events

Abstract: Local control of neural blood flow is considered to reside in innervation of epineurial and endoneurial arterioles rather than in intrinsic autoregulatory mechanisms. With the use of an isolated vessel preparation and an in vivo approach, the present studies examined intrinsic vasomotor responsiveness of epineurial arterioles. Segments of epineurial arterioles, cannulated on glass micropipettes (40 μm) and pressurized in the absence of intraluminal flow, showed sustained pressure-dependent (30–90 mmHg) vasocon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…A dose of 3 ϫ 10 Ϫ7 M NE completely constricted the epineurial arterioles and terminated local blood flow in sciatic nerves. The NE-induced responses obtained in the present study were quite compatible with other reports (16,38). It has been reported that endoneurial arterioles control the blood flow of sciatic nerves as well as the epineurial arterioles (2,46).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…A dose of 3 ϫ 10 Ϫ7 M NE completely constricted the epineurial arterioles and terminated local blood flow in sciatic nerves. The NE-induced responses obtained in the present study were quite compatible with other reports (16,38). It has been reported that endoneurial arterioles control the blood flow of sciatic nerves as well as the epineurial arterioles (2,46).…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, superfusion with LKS did not affect the diameters of epineurial arterioles in the present study. Wang et al (38) used a physiological buffer solution bubbled with 95% N 2 -5% CO 2 to measure in vivo blood flow of rat sciatic nerves with laser Doppler flowmetry, as did the present study, which superfused them with LKS. In a study using hydrogen-clearance methods, other investigators (3) filled the measuring area of sciatic nerves with mineral oil.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Nevertheless, normalization of the data in Fig. 2B to PD at 70 mmHg [i.e., classic myogenic reactivity curves (48)] reveals that the OH rat arteries exhibited significantly augmented myogenic constriction (Fig. 4C).…”
Section: Myogenic Responsesmentioning
confidence: 99%